REINTERPRETASI HADIS TENTANG AKHLAK DALAM KITAB SUNAN TIRMIDZI NO. INDEKS 2003 - Erfan Fausi (DIRAYAH : Jurnal Ilmu Hadis, 2024)
This research aims to reinterpret the hadith about morals contained in the hadith narrated by Sunan Tirmidzi. Hadith is the main source of teachings in Islam which provides guidance on good behavior and correct morals. However, understanding and interpretation of hadith are often influenced by different social, cultural and historical contexts. In this research, an in-depth analysis was carried out of the hadiths contained in Sunan Tirmidzi which relate to morals. The approach used is literature review and qualitative analysis methods to understand the original meaning of the hadith and analyze its historical context. Apart from that, comparisons are also made with related hadiths from other sources to obtain a comprehensive understanding. So that it contributes to updating the understanding of morals in Islam by taking into account the context of the times and the increasingly complex demands of society. From the results of the analysis obtained through sanad and matan criticism, the status of the hadith narrated by Sunan Tirmidzi no. The 2003 index studied was Hasan Li Dhatihi. Therefore, it can be concluded that the hadith narrated by al-Tirmidzi index number 2003 which explains morals has the status of maqbul/acceptable and can be used as evidence in everyday life.